1.) (-2,3)
2.) a=175/43 b= -70/43
3.)(7,3)
I believe i am right
I haven't one this in a long time
If i am can i get Brainliest
Answer:
(0, - 3 ) and (- 1, - 5 )
Step-by-step explanation:
Given the 2 equations
y = 4x² + 6x - 3 → (1)
y = 2x - 3 → (2)
Substitute y = 4x² + 6x - 3 into (2)
4x² + 6x - 3 = 2x - 3 ( subtract 2x - 3 from both sides )
4x² + 4x = 0 ← factor out 4x from each term
4x(x + 1) = 0
Equate each factor to zero and solve for x
4x = 0 ⇒ x = 0
x + 1 = 0 ⇒ x = - 1
Substitute these values into (2) for corresponding values of y
x = 0 : y = 2(0) - 3 = 0 - 3 = - 3 ⇒ (0, - 3 )
x = - 1 : y = 2(- 1) - 3 = - 2 - 3 = - 5 ⇒ (- 1, - 5 )
Answer:
(look below)
Step-by-step explanation:
i used to do ixl so heres an appropriate answer:
1 21
3 63
5 105
7 147
:3
![\Large\boxed{\tt Answer:~x=\frac{5}{7} }](https://tex.z-dn.net/?f=%5CLarge%5Cboxed%7B%5Ctt%20Answer%3A~x%3D%5Cfrac%7B5%7D%7B7%7D%20%7D)
![\tt Step-by-step~explanation:](https://tex.z-dn.net/?f=%5Ctt%20Step-by-step~explanation%3A)
Remember: PEMDAS - Parentheses, exponents, multiply/divide, add/subtract
Distribute: 9(1+x) = 9+9x
19 - 5x = 9 + 9x
Add 5x to both sides of the equation and subtract 9 from both sides.
19 - 5x + (5x) = 9 + 9x + (5x)
19 - (9) = 9 - (9) + 14x
10 = 14x
Divide both sides by 14 to get the variable on its own.
10/14 = 14x/14
10/14=x
5/7 = x